2019
DOI: 10.1029/2019ja026594
|View full text |Cite
|
Sign up to set email alerts
|

NSEE Yielding Electron Temperature Measurements at the Arecibo Observatory

Abstract: Narrowband stimulated electromagnetic emissions (NSEE), a component of radio emissions created during high‐frequency (HF) radiowave ionospheric modification experiments, occur within 1 kHz of the HF pump frequency. NSEE was observed and studied for the first time at the HAARP (High Frequency Active Auroral Research Program) facility in Alaska (Norin et al., 2009, https://doi.org/10.1103/PhysRevLett.102.065003; Bernhardt et al., 2010, https://doi.org/10.1103/PhysRevLett.104.165004). Magnetized stimulated Brillo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…Mahmoudian, Senior, et al (2019) observed IA and EIC emissions due to MSBS near 4f ce . At Arecibo, SBS emissions including IA and EIC have also been observed by Djuth et al (2018) and Mahmoudian, Nossa, et al (2019). Meanwhile, the correlation…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Mahmoudian, Senior, et al (2019) observed IA and EIC emissions due to MSBS near 4f ce . At Arecibo, SBS emissions including IA and EIC have also been observed by Djuth et al (2018) and Mahmoudian, Nossa, et al (2019). Meanwhile, the correlation…”
Section: Introductionsupporting
confidence: 58%
“…Mahmoudian, Senior, et al (2019) observed IA and EIC emissions due to MSBS near 4 f ce . At Arecibo, SBS emissions including IA and EIC have also been observed by Djuth et al (2018) and Mahmoudian, Nossa, et al (2019). Meanwhile, the correlation between SEE with electron temperature, plasma irregularities, HF‐induced plasma, and ion lines has also been investigated at EISCAT (Honary et al, 1995) and HAARP (Fu et al, 2018; Mahmoudian et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The descending layer in the white dashed box in Figure 3b starts from the resonance height when the heater turns on and then descends downwards producing discrete enhanced N r which is in consistent with observations of the BUM in Figure 3d and plasma lines in Figure 3e within the dashed white lines. The descending raw electron density near 3fce ${f}_{\mathrm{ce}}$ in Figure 3b shows similar descending raw electron density for 4 f ce (Mahmoudian, Nossa, et al., 2019; Mahmoudian, Senior, et al., 2019) at EISCAT.…”
Section: Experimental Results and Analysismentioning
confidence: 70%
“…Therefore it would be of interest to carry out a beat-wave experiment near an electron gyroharmonic to investigate whether significant power can be transferred from the pump to the probe through the SBS-1 process. The ionacoustic wave is used as part of a diagnostic of the electron temperature in the ionosphere during ionospheric heating experiments 34,36,75 , using the dependence of the dispersion of the mode on the ion-acoustic speed. There are also observations of electromagnetic sidebands where the separation was close to ion gyroharmonics [37][38][39][40][41][42][43][44][45][46][47] which gives information about the local magnetic field and ion composition.…”
Section: Discussionmentioning
confidence: 99%